Validated Finite Element Modeling of Lightweight Concrete Floors Stiffened and Strengthened with FRP - Zahid, Manar; Al-Zaidee, Salah (Engineering, Technology & Applied Science Research, 2023)
The main challenge in designing Light-Weight Concrete (LWC) is to adapt most of the design, production, and execution rules from normal-weight concrete. Carbon Fiber-Reinforced Polymer (CFRP) composites provide strength and stiffness to the composite system. This study investigated the stiffness of an LWC flat slab with CFRP when subjected to human-induced vibration. This was determined by finding the natural frequency of the slab and comparing it with the acceleration limit ratio (human perception of vibration) of 0.5% g. In most cases, vibration characteristics are examined using commercial software based on Finite Element Analysis (FEA) methods that are powerful tools, but the user needs to understand the underlying assumptions and methods implemented, especially for reinforced concrete floor systems where inherent attributes, such as cracking, play an important role in the determination of vibration characteristics. This study used Abaqus CAE. The main idea of this study was that such software cannot detect the behavior of cracks in structures over the years and the effect on frequencies, as stiffness depends on the modulus of elasticity and not on the moment of inertia. Therefore, the natural frequency equation has a component that constantly accounts for the level of cracking on concrete slabs. This component was theoretically determined with detailed calculations that are not provided in the Design Guide for Vibrations of Reinforced Concrete Floor Systems. Then, the constant that accounts for the level of cracking k1 was multiplied by the modulus of elasticity E and substituted in the latter’s place in Abaqus to ensure the right behavior of the slab with and without CFRP. This study also investigated the properties of CFRP and how to represent it in the Abaqus. The numerical results showed good agreement with FEA and the acceptance criteria for walking excitations increased when using CFRP on a floor system.